Equatorial plasma bubbles: a review - Bhattacharyya, A. (My University, 2022)
The equatorial plasma bubble (EPB) phenomenon is an important component of space weather as the ionospheric irregularities that develop within EPBs can have major detrimental effects on the operation of satellite-based communication and navigation systems. Although the name suggests that EPBs occur in the equatorial ionosphere, the nature of the plasma instability that gives rise to EPBs is such that the bubbles may extend over a large part of the global ionosphere between geomagnetic latitudes of approximately 15 . The scientific challenge continues to be to understand the day-to-day variability in the occurrence and characteristics of EPBs, such as their latitudinal extent and the development of irregularities within EPBs. In this paper, basic theoretical aspects of the plasma processes involved in the generation of EPBs, associated ionospheric irregularities, and observations of their characteristics using different techniques will be reviewed. Special focus will be given to observations of scintillations produced by the scattering of VHF and higher frequency radio waves while they propagate through ionospheric irregularities associated with EPBs, as these observations have revealed new information about the non-linear development of Rayleigh–Taylor instability in equatorial ionospheric plasma, which is the genesis of EPBs.
Keywords: equatorial ionosphere; plasma instability; irregularities; radio wave propagation; ionospheric scintillations